QUALITY EDUCATION IN THE TEACHING OF FINE ARTS - Roza Sadikova Ismailovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article analyzes a number of knowledge and skills that serve to increase the effectiveness of fine art classes in secondary schools, and also provides an extensive analysis and some recommendations on ways and means to increase the interest of schoolchildren in the fine arts, further develop their creative abilities, quickly develop desires and hobbies painting, the tasks facing the teacher, who occupies the main place in these processes.